Dental implant fractures: aetiology, treatment and case report - Goiato, Marcelo Coelho [UNESP]; Haddad, Marcela Filié [UNESP]; Gennari Filho, Humberto [UNESP]; Villa, Luiz Marcelo Ribeiro [UNESP]; Santos, Daniela Micheline dos [UNESP]; Pesqueira, Aldiéris Alves [UNESP] (JCDR Research and Publications, 2014)
Purpose: This study aimed to investigate the etiology, clinical manifestations, and treatment options of dental implants fractures through a literature review and to relate a clinical report. Methods: A literature review was performed using the Medline database and this paper describes a case demonstrating the management of implant fracture. Twenty two articles were selected in the present literature review. Results: Nowadays the use of dental implants to rehabilitate completely and partially edentulous patients became the best treatment option; however, this treatment is suitable to failure. The fracture of implant body is a possible complication. The fracture of implant body is a late complication and is related to the failure in implant design or material, non-passive fitting of the prosthetic crown and overloading. Clinically, prosthesis instability and spontaneous bleeding are observed. Three options of treatment have been indicated: complete removal of implant fragment, maintenance of implant fragment, and surface preparation of the fragment with insertion of a new abutment. Conclusion: The literature indicates the complete removal of the fragment as the best treatment option.